Building Consistent Characters through Open-Source Generative AI - Martini, Luca; La Tessa, Lara; Zolezzi, Daniele (International Journal of Emerging Technologies in Learning (iJET), 2024)
This paper presents a pipeline for creating consistent characters using open-source generative AI tools, aimed at enhancing educational content. Through the use of XTTS, Fooocus, and FaceFusion, a talking avatar of the marine biologist Raffaele Issel was developed, accurately replicating his facial and vocal features. This study demonstrates how these tools can generate high-quality, engaging educational materials with minimal technical expertise and resources. The methodology facilitates the creation of interactive avatars for use in graphic novels and comic books, enriching museum and educational experiences.